Pemberdayaan Lansia Dalam Upaya Penatalaksanaan Hipertensi Di Kelurahan Taratara Satu - Calvin Langingi, Ake Royke; Pongantung, Henny; Anastasia Terok, Kansia; Dewi Wowor, Meylani (Journal of Excellence Humanities and Religiosity, 2024)
Elderly is when a person becomes older and experiences a decline in physical function, which is characterized by a decrease in muscle mass and strength, maximum heart rate, increased body fat, and decreased brain function. The reason for choosing the service topic is because elderly people cannot do activities for long enough and have to do more activities at home, which causes them to feel anxious about their condition and experience stress, which has an impact on their quality of life. The service method used is the lecture and talk show method with elderly people suffering from hypertension. The result of this service activity is that there is an increase in knowledge about the management of hypertension in the elderly. This activity is very important to carry out, especially targeting elderly people with hypertension because the elderly are no longer able to carry out activities and are unable to comply with taking anti-hypertension medication, so they need to be provided with counseling or socialization regarding the management of hypertension.